Time series data based AI operation and maintenance system of cloud network collaboration platform - Ruiying CHENG; Pan ZHANG; Yu XIAO; Yujie QIAO; Anyi ZHANG (Dianxin kexue)
The expansion of cloud computing in enterprise applications is not only the expansion of platform scale, but also the extension of platform applications.“Cloud-network collaboration” and “micro-service” are important trends in the evolution of enterprise cloud platforms.As the importance of enterprise information construction continues to rise, the operation and maintenance of the microservice-oriented cloud-network collaboration platform faces great challenges.The challenges faced by the operation and maintenance were analyzed, the requirements for artificial intelligence operation and maintenance of the platform were sorted out, a technical system for artificial intelligence operation and maintenance of the platform based on time-series data analysis was proposed, and an artificial intelligence operation and maintenance subsystem for the cloud network collaborative platform was designed.The proposed technical system and system design are practical and generalizable, and can be used as a reference for the technical approach of enterprise cloud platform construction and optimization.